Molecular signature of the D-loop in the brown pencilfish Nannostomus eques (Characiformes, Lebiasinidae) reveals at least two evolutionary units in the Rio Negro basin, Brazil - Terêncio, Maria Leandra; Schneider, Carlos Henrique; Porto, Jorge Ivan Rebelo (Journal of Fish Biology, 2012)
The genetic variability of the brown pencilfish Nannostomus eques was studied, based on an analysis of sequences from the control region (1084 bp) of mitochondrial (mt)DNA in 125 individuals collected from eight tributaries along the upper (Açaituba, Miuá, Jaradi and Arixanã), middle (Demini), and lower (Jacundá, Maguari and Catalão) Rio Negro (Brazil). Phylogenetic inferences using mtDNA data from N. eques revealed two evolutionary units. Genetic distance between them ranged from 5·5 to 8·3% and differed by 8·5-11·8% from the sister species pencilfish Nannostomus unifasciatus. The time of divergence between the two evolutionary units was estimated to be the Middle Pliocene (c. 2·99 million years before present). Population genetic analysis (DNA polymorphism, AMOVA and Mantel test) showed high haplotype diversity (HD, >0·90) in each evolutionary unit, a strong population genetic structure in the Demini River that formed a monophyletic group and a correlation between genetic divergence and geographical distance in only one of these units (evolutionary unit 1). On the basis of molecular data, the rapids and waterfalls near São Gabriel da Cachoeira (Upper Rio Negro) were the main barriers to gene flow within evolutionary unit 1 in some localities. The emergences of the Branco River and the Anavilhanas Archipelago were apparently responsible for the discrepancy in distribution of the two evolutionary units, except at Jacundá, where the evolutionary units were sympatric. In view of the differences between the evolutionary units, N. eques cannot be treated as a single stock in the Rio Negro basin. These results may have important implications for the fishery management of this ornamental fish. © 2012 The Authors. Journal of Fish Biology © 2012 The Fisheries Society of the British Isles.
Keywords: Dna, Mitochondrial; Animals; Bayes Theorem; Characiformes; Classification; Dna Sequence; Evolution; Genetic Variability; Genetics; Haplotype; Phylogeny; Genetics, Population; River; Animal; Bayes Theorem; Biological Evolution; Characiformes; Dna, Mitochondrial; Genetic Variation; Genetics, Population; Haplotypes; Phylogeny; Rivers; Sequence Analysis, Dna; Characiformes; Lebiasinidae; Nannostomus; Nannostomus Unifasciatus; Pisces